Cd recombination laser in a plasma generated by an electron beam - Mancini, H. L., author; Rocca, Jorge J., author; Wernsman, B., author; IEEE, publisher (Colorado State University. Libraries, 1986)
Laser action was obtained in the 1.40, 1.43, and 1.65 μm lines of CdI following electron-ion recombination in a plasma generated by an electron beam. Lasing does not occur during the excitation pulse due to the electron impact population of the laser lower levels. In this plasma, supercooling of the electrons is achieved under stationary conditions, and efficient CW recombination laser action might also be possible on lines in which the lower level is not significantly populated by electron collisions. Seven new infrared laser lines in CdII are also reported.